2001
DOI: 10.1097/00005768-200112000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training, vascular function, and functional capacity in middle-aged subjects

Abstract: These results suggest that moderate intensity circuit training designed to minimize the involvement of the arms improves functional capacity, body composition, and strength in healthy, middle-aged subjects without significantly influencing upper limb vascular function. This finding contrasts with previous studies in subjects with type 2 diabetes and heart failure that employed an identical training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 29 publications
6
61
1
6
Order By: Relevance
“…The consistence of previously published data 17,25 , shown above, indicate that exercise training improves endothelial function in heterogeneous groups, including groups where patients presented this dysfunction due to injury, corroborating with the results of our study and contrasting with studies of exercise training in subjects with normal endothelial function. One cannot forget to highlight that the improvement in vascular function is evident in every vasculature, even if exercise is only practiced in the inferior limbs, excluding the remaining of the body.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The consistence of previously published data 17,25 , shown above, indicate that exercise training improves endothelial function in heterogeneous groups, including groups where patients presented this dysfunction due to injury, corroborating with the results of our study and contrasting with studies of exercise training in subjects with normal endothelial function. One cannot forget to highlight that the improvement in vascular function is evident in every vasculature, even if exercise is only practiced in the inferior limbs, excluding the remaining of the body.…”
Section: Discussionsupporting
confidence: 92%
“…The size of the sample was calculated with base in previous studies [15][16][17] . The data were initially evaluated for the test of Kolmogorov--Smirnova to establish the normality.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators reported the following effects of physical training on the vascular function. In middle-aged subjects, 8-week moderate intensity circuit training did not alter the endothelium-dependent or -independent vascular function while muscle strength was increased significantly (Maiorana et al 2001). In patients receiving hemodialysis, 4 -6 week handgrip exercise training had no effect on endothelium-dependent flow or peak reactive flow in response to 5-min arterial occlusion, but both were increased in control subjects (Bank et al 1998).…”
Section: Vascular Functionmentioning
confidence: 83%
“…A lesão do endotélio vascular prejudica a vasodilatação do vaso, e esta lesão pode ser associada com fatores de riscos para doenças vasculares, como na obstrução coronariana, lesão cardíaca crônica, e diabetes tipo 2 (MAIORANA et al, 2001).…”
Section: Formação E Vias De Produção Do óXido Nítricounclassified
“…Isso ocorreu após terem realizado treinamento de circuito de resistência em aparelhos de musculação com 7 exercícios gerais para membros inferiores, tronco, e membro superiores, todos em moderada intensidade, 3 vezes por semana durante 8 semanas (MAIORANA et al, 2001). Neste trabalho, ficou caracterizado que, exercícios isolados não apresentam melhoras significativas nas respostas cardiovasculares ao treinamento físico.…”
Section: Alterações Na Disponibilidade Do óXido Nítrico Após Treinameunclassified